Pilot Investigation of Changes in Readiness and Confidence to Quit Smoking After E-Cigarette Experimentation and 1 Week of Use. Issue 1 (22nd October 2013) - Wagener, Theodore L.; Meier, Ellen; Hale, Jessica J.; Oliver, Elisha R.; Warner, Maggie L.; Driskill, Leslie M.; Gillaspy, Stephen R.; Siegel, Michael B.; Foster, Steven
Abstract: Introduction: This study examined changes in smokers' readiness and confidence to quit smoking, smoking behavior, nicotine withdrawal symptoms, and tobacco product preference following electronic cigarette (EC) experimentation and 1 week of ad libitum use. Methods: Current cigarette smokers, with no prior use of ECs and uninterested in quitting, completed 3 study phases: baseline assessment ( N = 20), experimentation ( N = 19), and ad libitum use ( N = 16). Baseline assessment consisted of completion of assessment measures and exhaled carbon monoxide measurements. Experimentation phases consisted of four, 75-min sessions in which participants completed assessment measures and sampled 3 EC brands and their own brand of cigarette (OBC). Ad libitum use included participants selecting and being provided their preferred EC brand from the experimentation phase to be used "as you want" for 1 week. Outcome measures included readiness and confidence to quit smoking, nicotine withdrawal symptoms, product preference/satisfaction, and smoking behavior items. Results: Readiness and confidence to quit increased significantly during the experimentation period and continued to increase during ad libitum use. There were no significant differences in reported effectiveness in reducing smoking urges and cravings between OBC and EC though OBC were rated as more enjoyable and satisfying. During ad libitum use, regular cigarette smoking decreased by approximately 44% from baseline levels with overall tobacco use (EC + OBC) remaining the same. Conclusions: Among a small convenience sample of unmotivated cigarette smokers, EC experimentation and 1 week of ad libitum use increased readiness and confidence to quit regular cigarettes and reduced regular cigarette smoking.